Global Effect of Inauhzin on Human p53-Responsive Transcriptome - Liao, Jun-Ming (Public Library of Science, 2012)
BACKGROUND: Previously, we reported that Inauhzin (INZ) induces p53 activity and suppresses tumor growth by inhibiting Sirt1. However, it remains unknown whether INZ may globally affect p53-dependent gene expression or not. Herein, we have conducted microarray and real-time PCR analyses of gene expression to determine the global effect of INZ on human p53-responsive transcriptome. METHODOLOGY/PRINCIPAL FINDINGS: In this study, we conducted microarray analysis followed by PCR validation of general gene expression in HCT116(p53+/+) and HCT116(p53−/−) cells treated with or without INZ. Microarray data showed that 324 genes were up-regulated by ≥2.3-fold and 266 genes were down-regulated by ≥2-fold in response to INZ treatment in a p53-dependent manner. GO analysis for these genes further revealed that INZ affects several biological processes, including apoptosis (GO:0006915), cell cycle (GO:0007049), immune system process (GO:0002376), and cell adhesion (GO:0007155), which are in line with p53 functions in cells. Also, pathway and STRING analyses of these genes indicated that the p53-signaling pathway is the most significant pathway responsive to INZ treatment as predicted, since a number of these p53 target genes have been previously reported and some of them were validated by RT-qPCR. Finally, among the 9 tested and highly expressed genes, ACBD4, APOBEC3C, and FLJ14327 could be novel p53 target genes, for they were up-regulated by INZ in HCT116(p53+/+) cells, but not in HCT116(p53−/−) cells. CONCLUSIONS/SIGNIFICANCE: From our whole genome microarray analysis followed by validation with RT-qPCR, we found that INZ can indeed induce the expression of p53 target genes at a larger scale or globally. Our findings not only verify that INZ indeed activates the p53 signaling pathway, but also provide useful information for identifying novel INZ and/or p53 targets. The global effect of INZ on human p53-responsive transcriptome could also be instrumental to the future design of INZ clinical trials.